LITERATURE REVIEW MOTIVATION AND PERFORMANCE DETERMINATION: TRAINING ANALYSIS AND PERFORMANCE ASSESSMENT - Lilis Kurniawati (Dinasti International Journal of Management Science, 2022)
Previous and relevant research has a great influence on the research to be carried out. Previous research serves to strengthen the theory of the relationship between variables. This pre-research was conducted with the aim of building a hypothesis with a descriptive method. This pre-research aims to determine the effect of the variables, namely training and performance appraisal, on motivation and performance. The results of this library research are: 1) Training has an effect on motivation; 2) Rating k performance has an effect on motivation; 3) Training has an effect on performance; 4) Rating k performance affects performance; and 5) Motivation has an effect on performance .